Neuropharmacologically Active Complexes of Cu(II) and Zn(II) with Substituted 1,4-Benzodiazepine-4-oxides - Hukuman, Zeinul; Sharma, L.M. (Asian Journal of Chemistry, 2016)
Synthesis of Cu(II) and Zn(II) complexes with 7-chloro-1,3-dihydro-5-phenyl-2H-1,4-benzodiazepin-2-one-4-oxide having ML4X2 stoichiometries has been reported (where X = Cl–, NO3– and CH3COO–). Characterizations have been done on the basis of elemental analysis, conductivity, magnetic, IR and electronic spectral studies. Complexes have been found as neuropharmacologically more effective in taming and hypnotic activities and posses much higher toxicity as compared to the ligand.